Estimating Self and Spouse Intelligence among Jordanians - Firas Al-Hamouri; Adnan Atoum; Mohammad Melhem; Hamzeh Rababa (Sultan Qaboos University, 2016)
The current study aimed at exploring self and spouse estimates of general and multiple intelligences among a sample of married Jordanian Students. Two-hundred and ten participants, recruited from Yarmouk and Al-Balqaa Universities, Jordan, completed a brief questionnaire based on those used in previous research which included an estimation of general IQ and each of the multiple intelligence sub-types. Results of the study partially replicated the results from other multiple intelligence self-estimate studies showing sex differences on general and logical intelligences, and confirmed previous research results that estimated verbal (linguistic) intelligence followed by numerical (logical) intelligence are the best significant predictors of estimated general intelligence. These results were discussed in terms of sex and cultural differences and some recommendations were made